Association of NF-κB polymorphisms with clinical outcome of non-medullary thyroid carcinoma. Issue 7 (July 2017) - Plantinga, Theo S; Petrulea, Mirela S; Oosting, Marije; Joosten, Leo A B; Piciu, Doina; Smit, Johannes W; Netea-Maier, Romana T; Georgescu, Carmen E
Abstract : The NF-κB inflammatory pathway plays a major role in cancer development and clinical progression. Activation of NF-κB signaling is promoted by NFKB1 and inhibited by NFKBIA. The present study aimed to determine the relevance of NFKB1 rs4648068 and NFKBIA rs2233406 genetic variants for non-medullary thyroid cancer (NMTC) susceptibility, progression and clinical outcome. This case–control and cohort study consists of a Romanian discovery cohort (157 patients and 258 controls) and a Dutch validation cohort (138 patients and 188 controls). In addition, patient cohorts were analyzed further for the association of genetic variants with clinical parameters. Functional studies were performed on human peripheral blood mononuclear cells. No associations were observed between the studied genetic variants and TC susceptibility. Although no statistically significant associations with clinical parameters were observed for NFKB1 rs4648068, the heterozygous genotype of NFKBIA rs2233406 was correlated with decreased radioactive iodide sensitivity requiring higher cumulative dosages to achieve clinical response. These findings were discovered in the Romanian cohort ( P < 0.001) and confirmed in the Dutch cohort ( P = 0.01). Functional studies revealed that this NFKBIA rs2233406 genotype was associated with elevated TLR4-mediated IL-1β production. In conclusion, genetic variation in NFKBIA, an inhibitor of NF-κB signaling, is associated with clinical response to RAI therapy and with increased production of the pro-inflammatory cytokine IL-1β, providing a potential mechanism for the observed clinical associations. These data suggest that NF-κB signaling is involved in NMTC pathogenesis and that the inflammatory tumor microenvironment could contribute to RAI resistance.